DISTINCTIVE FEATURES OF CENTRAL ASIAN ARCHITECTURE - Zohidjon Madrahimov; Kozimjon Olimov (Scholar Express Journal, 2023)
This article covers the distinctive features of Central Asian architecture-that is, Styles and views in the area-from other regions to farli aspects. You can also get methods, discussions, solutions and information on the architecture of Central Asia in the article
Keywords: Central Asia; architecture; cultural influences